Rancang Bangun Digital Firing Angle Sebagai AC "“ AC Controller Untuk Alat Pengering Sepatu Dengan Metode Kontrol Proporsional Integral - Nugroho, Mochamad Ari Bagus; Hasnira, Hasnira; Iraqi, Mohammad Zainul; Suhariningsih, Suhariningsih (JURNAL INTEGRASI, 2024)
The rainy season is an obstacle for everyone, especially drying shoes, because rain can hinder the process of drying shoes. Currently, shoes are still dried using the conventional method, namely by utilizing the sun's heat. The next development is a system for drying shoes using gas fuel, but it has the potential for fire. In this final project, a shoe drying system is designed which is controlled using PI control according to a specified setpoint to dry shoes when exposed to rain or at night. To get the appropriate room temperature, the output voltage from the heater needs to be controlled using the Digital Firing Angle. The ignition angle is regulated by the Digital Firing Angle circuit. To maintain the temperature conditions in a stable condition, namely 65°C, this tool is controlled using PI (Proportional Integral) control. This dryer is designed for a maximum of 1 pair of wet shoes. With final humidity results in the drying room â‰¤ 20%RH. With this final project, it can dry shoes in rainy conditions in 94 minutes for synthetic leather shoes and 104 minutes for leather shoes.